Targeting Platinum Resistant Disease in Ovarian Cancer - Morgan, S.L.; Medina, J.E.; Taylor, M.M.; Dinulescu, D.M. (Current Medicinal Chemistry, 2014)
Ovarian cancer is an extremely aggressive disease in which the vast majority of patients face a very poor prognosis. Although most patients initially respond to current chemotherapeutic regimens that include a combination of platinum- based therapy (cisplatin/carboplatin) and paclitaxel, the vast majority of them quickly relapse and develop increased resistance to available treatments. Thus, intrinsic and acquired chemotherapy resistance is a major obstacle in the treatment of ovarian cancer patients. Consequently, the priorities for basic and translational ovarian cancer research need to include the identification of novel therapies directed against key molecular targets and signaling pathways in platinum resistant disease. At the same time, we need to develop novel systems for drug delivery aimed at increasing the efficacy and reducing the toxicity of platinum-based treatments. Improving the current responses to platinum chemotherapy is critical not only for achieving a better outcome clinically, including a longer survival, but also for allowing patients to have a better quality of life while in treatment.
Keywords: platinum resistance